Smart distributed embedded systems for healthcare applications - Nagrath, Preeti; Alzubi, Jafar; Singhla, Bhawna; Rodrigues, Joel, 1972-; Verma, A. K. (Ajit Kumar) (Explainable AI (XAI) for engineering applications, 2023)
"The text covers new techniques that will be helpful for patient's early diagnosis of diseases and start treatments with the help of distributed technology. It will serve as an ideal reference text for graduate students and researchers in diverse engineering fields including electrical, electronics and communication, computer, and biomedical"--